Control of Excited‐State Conformations in B, N‐Acenes. (20th February 2019) - Lu, Zhenpin; Quanz, Henrik; Ruhl, Julia; Albrecht, Georg; Logemann, Christian; Schlettwein, Derck; Schreiner, Peter R.; Wegner, Hermann A.
Abstract: We present a new concept to control the conformations of molecules in the excited state through harvesting negative hyperconjugation. The strategy was realized with the 2, 3, 1, 4‐benzodiazadiborinane scaffold, which was prepared by a new synthetic procedure. Photochemical studies identified dual light emission, which was assigned to well‐defined conformers. The emission at longer wavelength can be switched off by restricting the rotational degrees of freedom in the solid state as well as by controlling the energy levels of the excited states through adjusting the solvent polarity.